Successful Control of Dasatinib-related Chylothorax by the Japanese Herbal Medicine "Goreisan" - Sasaki, Hisashi; Kimizuka, Yoshifumi; Ogata, Hiraku; Okada, Yosuke; Ota, Shinichiro; Sano, Tomoya; Watanabe, Chie; Maki, Yohei; Yamamoto, Takayuki; Tagami, Yoichi; Miyata, Jun; Hayashi, Nobuyoshi; et al. (Internal Medicine, 2019)
Dasatinib-related chylothorax is a rare adverse event, and the mechanism underlying its occurrence is still not fully understood. We herein report the case of a 73-year-old woman with chronic myeloid leukemia (CML) who developed dasatinib-related chylothorax refractory to conventional treatments, except for steroids. To the best of our knowledge, this is the first case of dasatinib-related chylothorax which was successfully controlled by combining diuretics with the Japanese herbal medicine "Goreisan." "Goreisan" is known to inhibit aquaporin channels and regulate the water flow. Our findings showed that "Goreisan" is an effective treatment option for uncontrollable dasatinib-related chylothorax.